СONSIDERATION OF CIVIL CASES ABOUT ADOPTION WITH PARTICIPATION OF THE PROSECUTOR - Sarimova Марал Орынбасаровна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
In the article considers the legal institute of adoption with participation of the prosecutor.